Menopausal Knowledge and Attitudes of Women During the Perimenopausal Period - MİRAL, MUKADDES TURAN; BAYRAKTAR, TUĞBA (Lippincott Williams & Wilkins, 2024)
Objective: This study aims to determine the relationship between knowledge and attitudes about menopause among women in the perimenopausal period. Methods: A descriptive and relationship-seeking cross-sectional study was conducted in family health centers in a district of Istanbul between January and March 2023. The study included 300 women in the perimenopausal period. Data were collected through face-to-face interviews using a descriptive information form, a menopause knowledge test, and the Menopause Attitude Scale. Results: The average age of participants was 45.07 +/- 3.50, with 85.3% married, 37.0% having completed primary school, and 55.0% being housewives. The average menopause knowledge score was 12.29 +/- 3.75 (out of 20), and the average menopause attitude score was 25.23 +/- 6.99 (out of 52). No significant relationship was found between menopause knowledge and attitude scores (r = 0.06, P > 0.05). Women with an income exceeding their expenses had higher menopause knowledge scores (P < 0.05). Unmarried women, those with lower education levels, those with higher incomes, and those living alone had higher menopause attitude scores compared with their counterparts (P < 0.05). Conclusions: Women's knowledge and attitudes toward menopause are moderate in the perimenopausal period. There is no significant relationship between menopausal knowledge and attitude of women during the perimenopausal period. It was determined that menopause knowledge level differed according to women's income status, and menopause attitude differed according to marital status, educational status, and cohabitation status in this study.
Keywords: Attitude; Knowledge; Menopause; Perimenopause; Women